Pastures anti-A therapy. Product (2d part) - Gálvez Calla, Luis H. (2006)
The final formulation that includes Sangre de grado watery extract, excipients and preservants; Pasta Terapéutica Anti-A (PTA) was denominated, that profit later to take place the tests of accelerated stability, every 30 days by space of three months, that consisted of conserving the bottles containing the formulation of a same lot of manufacture to room temperature and 4 º C of refrigeration and to evaluate the consistency, aspect, color, scent and bactericidal activity. This last one was made by means of the method of diffusion in agar and the technique of excavation plate culture, in front of positive bacteria negative Gram and Gram. The results were satisfactory for Gram positive, like Staphylococcus aureus ATCC 6538, Staphylococcus epidermides ATCC 12228 and Bacillus subtilis ATCC 6633, in the case of single Gram negative I am observed antimicrobial activity forehead a Escherichia coli ATCC 8739. but not thus for Pseudomona aeruginosa.